Clinical features of Korean patients with rhinophyma. Issue 6 (27th December 2016) - Kim, Na Hee; Yun, Sook Jung; Lee, Jee‐Bum
Abstract: Rhinophyma results from hyperplasia of the sebaceous glands and connective tissue. Clinical features in Asian rhinophyma patients are largely underreported. In this study, we aimed to evaluate the clinical features of rhinophyma in Korean patients. We reviewed clinical photos and medical records of 39 Korean patients diagnosed with rhinophyma and assessed the severity and clinical course by using the classical National Rosacea Society index. The male : female ratio was 6.8:1, and over 90% of the patients were older than 40 years. The mild‐grade rhinophyma was the most dominant (46.1%), followed by the moderate (41.0%) and severe (12.8%) grades. Disease progression to severe grade occurred over an average of 8.2 years. Furthermore, 70% of all cases revealed lesion distribution limited to the nose. As disease severity progressed to higher grades, the extent of nasal involvement increased (Pearson correlation coefficient, 0.685). Rhinophyma is a slowly progressing disease showing male predominance unrelated to specific trigger factors. In many cases, this disease often exclusively affects the nose in Asian patients.